الإمداد المائي مابين التحديات والصعوبات في ليبيا في الفترة (2019-2021) - كريمة أحمد بركة; ميلاد أحمد أبوكلش; الطاهر محمد الحميدي; سالم سعيدة; عبدالرزاق أبوشاقور (The Libyan Journal of Science, 2024)
Water is an essential resource for economic, industrial, and social development in all nations. However, Libya is considered a water-scarce country due to its limited and non-renewable water resources, with around 92% of its supply derived from groundwater. The General Company for Water and Sanitation oversees the distribution of water from various sources, which include 60% from the Great Man-Made River, 10% from seawater desalination, and 30% from groundwater wells. In recent years, there has been a significant decline in water supply. This study examines the distribution practices of the General Company for Water and Sanitation across different regions, particularly during the challenges faced from 2019 to 2021. The average water supply per person is estimated to be about 250 liters daily. Data shows fluctuations in the available water supply, leading the company to explore solutions to improve water availability. By 2021, the distribution sources had changed to 50% from groundwater, 49% from the Great Man-Made River, and 1% from seawater desalination. After accounting for technical losses, the water deficit in 2021 was approximately 6%. The company is actively working to mitigate this deficit by addressing the challenges it faces and developing proposals and solutions to enhance water supply efficiency.